2017
DOI: 10.1016/j.jgo.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Activities, function, and health-related quality of life (HRQOL) of older adults with cancer

Abstract: Purpose This study aims to (1) describe the activities, function, and health-related quality of life (HRQOL) of a large sample of older adults (age ≥ 65) with cancer, (2) identify the associations with demographics, cancer type, comorbid conditions, and ability to participate in activities and functional status. Methods The Health Registry/Cancer Survivorship Cohort is an institutional database designed to aid cancer survivorship research. The registry includes three measures of patient-reported HRQOL: FACT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 42 publications
5
80
1
7
Order By: Relevance
“…Moreover, because respondents were surveyed at different times along the cancer journey, the results herein indicate that symptom assessment followed by appropriate supportive interventions is important in the lives of older survivors. A significant association between increased comorbidities and poorer HRQOL has been demonstrated in several previous studies . Currently, to the best of our knowledge, only limited literature exists regarding the quality of care for comorbid conditions among cancer survivors, with such quality varying across cancer types and physician specialty .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, because respondents were surveyed at different times along the cancer journey, the results herein indicate that symptom assessment followed by appropriate supportive interventions is important in the lives of older survivors. A significant association between increased comorbidities and poorer HRQOL has been demonstrated in several previous studies . Currently, to the best of our knowledge, only limited literature exists regarding the quality of care for comorbid conditions among cancer survivors, with such quality varying across cancer types and physician specialty .…”
Section: Discussionsupporting
confidence: 62%
“…A significant association between increased comorbidities and poorer HRQOL has been demonstrated in several previous studies. 4,29,30 Currently, to the best of our knowledge, only limited literature exists regarding the quality of care for comorbid conditions among cancer survivors, with such quality varying across cancer types and physician specialty. 31,32 In the current study, HRQOL also was found to be compromised in those who expressed support needs related to debilitated physical health (eg, the need to have someone to help when fatigued).…”
Section: Discussionmentioning
confidence: 99%
“…Survivors with lower income, less education, or more comorbid conditions; those who are unemployed; and those who are uninsured or underinsured have higher ongoing symptom burden . Survivors who are from racial/ethnic minority groups or are socioeconomically disadvantaged and those with more comorbid conditions report worse quality of life …”
Section: The Growth Of Cancer Survivorship Researchmentioning
confidence: 99%
“…31 Survivors who are from racial/ethnic minority groups or are socioeconomically disadvantaged and those with more comorbid conditions report worse quality of life. 36,37 In addition to ongoing symptoms and functional impairment after the successful completion of anticancer treatment, survivors are at increased risk for several cancer-related issues. For many cancer survivors, the initial course of treatment is successful, and the cancer never recurs.…”
Section: The Growth Of Cancer Survivorship Researchmentioning
confidence: 99%
“…The estimate is slightly higher in older adults, in which 64% of older adults with cancer report some form of functional limitation. 2 If unaddressed, these functional limitations can affect productivity, 3,4 quality of life, 5,6 and overall survival. 7 Rehabilitation services have the potential to reduce the functional limitations experienced by cancer survivors.…”
Section: Introductionmentioning
confidence: 99%